2016
DOI: 10.1111/dth.12440
|View full text |Cite
|
Sign up to set email alerts
|

Impending skin necrosis after dermal filler injection: A “golden time” for first-aid intervention

Abstract: Vascular compromise with impending skin necrosis is one of the most serious potential complications. Early recognition of vascular occlusion and swift and aggressive treatment are required to avoid any irreversible changes. However, initial symptoms of a vascular event are often dismissed as simple post-procedural discomfort. If more than 3 days pass after filler injection, crust formation is initiated over the erythematous base along with a rim of fibrous tissue. Due to the replacement of normal tissues by fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 6 publications
0
13
0
1
Order By: Relevance
“…In an experimental study about free flap skin survival, more than 9 hours of warm ischemia was found to severely affect the survival of the skin component. 9 Although most studies suggest injection of hyaluronidase, there is no unanimity on dosage and the interval between 2 doses. 10 It can be injected on an hourly basis till the endpoint of treatment showing reperfusion of skin and correction of blanching/livedo.…”
Section: Discussionmentioning
confidence: 99%
“…In an experimental study about free flap skin survival, more than 9 hours of warm ischemia was found to severely affect the survival of the skin component. 9 Although most studies suggest injection of hyaluronidase, there is no unanimity on dosage and the interval between 2 doses. 10 It can be injected on an hourly basis till the endpoint of treatment showing reperfusion of skin and correction of blanching/livedo.…”
Section: Discussionmentioning
confidence: 99%
“…Then it The compression of suprathroclear, supraorbital or glabellar arteries can lead to glabellar necrosis, but also in this case in the opinion of the authors quit all the cases of necrosis are due to an intraarterial injection [18]. This is why luckily a good injection technique and the right plane of injection can preserve physicians from this risk [13] [ Figure 5].…”
Section: Facial Arterymentioning
confidence: 92%
“…National Library of Medicine's PubMed database was utilized to have an overview of the effi cacy, safety and outcomes and to fi nally fi nd out the optimal use of hyaluronidase.  Use hyaluronic acid based product that is a temporary and biodegradable product and can be in part break down by hyaluronidase [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Guidelinesmentioning
confidence: 99%
“…Other reports have estimated treatment with 500 units of high-dose pulsed hyaluronidase for a vascular territory similar to the present case. Therefore, we adhered to that protocol [9].…”
Section: Daily Follow-upmentioning
confidence: 99%